COAGULATION-FLOCC ULATION EFFICIENCY LEVEL OF WATER TREATMENT PLANTPROTOTYPE - Sutapa, Ignasius Dwi Atmana (Teknologi Indonesia, 2014)
Surface water is a potential water source for public to be processed into clean water. Coagulation-Flocculation is an important process in drinking water treatment because it has major influence on the purification process and quality of produced water. The objective of the study is to assess the efficiency of coagulation-flocculation processes in compartments which is arranged in series of flocculators tank, a sedimentation tank, and water production tank. A prototype of water treatment plant with capacity of 30 l/min was used in the experiment. The results showed that the composition of the six series compartments flocculator was able to give better efficiency of coagulationflocculation process. Process of species forming and destabilization of colloidal particles occured in compartmentK0 and K1. Flocculation process started in compartment K2. Raw water turbidity was in the range of 18 NTU, gradually decreased to 6 NTU with 66.67% efficiency rate. Water turbidity decreased during the sedimentation and filtration processes. Result in final processing was almost 0 NTU with the level of efficiency close to 100% and the pH value of the clean water was 7.3.